Estudio de los parámetros de crecimiento sobre las propiedades de recubrimientos Ag-DLC y Cr-DLC depositados por Magnetron Sputtering - Calderón Ipanaque, Noely Zully (2018)
The aim of this thesis is to set-up and put in operation a magnetron for targets of 2” diameter in order to produce metal-diamond like carbon (Me-DLC) films using the technique of magnetron sputtering. For this thesis were used targets of silver (Ag) and chromium (Cr) with 99.99% purity. Ag-DLC and Cr-DLC films have been deposited onto 2” diameter silicon wafers. The internal stress and the hardness of the films have been measured using the wafer curvature method and nanoindentation, respectively. The morphology and thickness of the films were measured by scanning electron microscopy (SEM). The composition and chemical structure were measured by Auger and Raman spectroscopy, respectively. The results for the Ag-DLC films show that the conditions to obtain a high hardness are associated to changes in their chemical composition product of the application of a bias voltage to the substrate. In the case of Cr-DLC films, internal stress passes from tensile (positive) in the absence of acetylene gas, to compressive (negative) as the acetylene gas flow increases. While with the increase of the bias voltage, the compressive stress in Cr-DLC films increases in absolute value. The results are explained in terms of the effects of the deposition parameters on the chemical and structural composition in Ag-DLC and Cr-DLC films.